2016
DOI: 10.11648/j.js.s.2016040101.11
|View full text |Cite
|
Sign up to set email alerts
|

Onlay versus Sublay Mesh Repair for Ventral Hernia

Abstract: Abstract:Introduction: Ventral hernia repair is among the most common surgical operations performed worldwide and the two operative techniques most frequently used in case of ventral hernia are the onlay and sublay repair. However, it remains unclear which technique is superior. The aim of this study was to compare the outcome of the onlay versus sublay mesh repair for ventral hernia. Patients and Methods: A total of 200 patients with paraumbilical, epigastric and supraumbilical incisional hernias were divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 14 publications
0
30
0
Order By: Relevance
“…8 Study by Saber A et al found that the mean operative time for onlay repair was 67.04±13.19 minutes ranged from 45 to 90 minutes while in sublay group was 93.26±24.94 minutes ranged from 60 to140 minutes (P≤0.0001). 9 In previous studies, the mean operative time was longer in sublay than onlay techniques due to the time consumed to create the preperitoneal tunnel. 6,7,10 Our data came in agreement with these reported studies as the operative time in sublay group patients was much longer in the onlay technique.…”
Section: Discussionmentioning
confidence: 96%
“…8 Study by Saber A et al found that the mean operative time for onlay repair was 67.04±13.19 minutes ranged from 45 to 90 minutes while in sublay group was 93.26±24.94 minutes ranged from 60 to140 minutes (P≤0.0001). 9 In previous studies, the mean operative time was longer in sublay than onlay techniques due to the time consumed to create the preperitoneal tunnel. 6,7,10 Our data came in agreement with these reported studies as the operative time in sublay group patients was much longer in the onlay technique.…”
Section: Discussionmentioning
confidence: 96%
“…The explanation of this reduced incidence of infection in sublay than in onlay technique that the former has several advantages, one of which being not transmitting the infection from subcutaneous tissues down to the mesh, as it lies quite deep in the preperitoneal plane [15,16,23,24]. Also, Milad and his colleagues reported that the retromuscular plane is highly vascular and helps preventing infection, and if any infection occurs in the subcutaneous plane, it will not affect the mesh, as the mesh is retromuscular in a deeper plane [1,25].…”
Section: Discussionmentioning
confidence: 99%
“…Hemostasis was secured and wound was closed over a suction drain. A dose of broad-spectrum antibiotic was given prior to anaesthesia [1].…”
Section: Onlay Mesh Repairmentioning
confidence: 99%
See 2 more Smart Citations